A Closer Look at Students’ Silence: A Case Study - Ahmad Faizin, Halim; Permatasari, Ita; Widodo, Yulius Harry (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
This article discusses Indonesian State Polytechnic students understanding and reasons towards silence and lack of oral participation in class. It is a qualitative case study conducted with two students from English study program. The authors conducted semi-structured interview and then analyzed the data using a constant comparisons method. Both students realize that they were one of the quietest students in the class. It is revealed that the causes of their silence are lack of speaking skills that related to their study program, shyness in the classroom and lack of background knowledge related with their fields. Their silence in classroom could not be interpreted as their unwillingness to contribute in class, rather than a process they should go through whenever they use English at class orally. Besides indicate the need to find a more suitable teaching approach to help students in class, this finding also suggest that teachers or lecturers need to understand the reason behind students’ silence better.